Retrospective analysis of oral cavity squamous cell carcinoma treated with surgery and adjuvent radiotherapy - Sharma, Mohit; Deshpandey, Abhinav; Gupta, Nayan; Patel, Mahesh (International Journal of Research in Medical Sciences, 2016)
Background: Oral cavity cancer is one of the leading causes of cancer related deaths in developing countries. Most of the failures occur due to locoregional recurrence. The present study was conducted to find out the pattern of recurrences and factors responsible for that in oral cavity squamous cell carcinoma (SCC). Methods: The study was conducted at Gujarat cancer and research institute Ahmedabad, India. Total 260 patients were evaluated in study from year January 2013 to December 2013 retrospectively. Two year follow up was studied to find out the pattern of failure in terms of local, regional (nodal) and systemic. Results: Oral cavity SCC has high chances of local failure when removed inadequately during surgery. Perineural spread, lymphovascular involvement and perinodal spread are important prognostic factors. Conclusions: Most patients of oral cavity cancer present in advanced stages. Close margins and perineural involvement are responsible for local recurrences while perinodal spread and lymphovascular involvement contributes to nodal recurrences. Tobacco consumption is important responsible factor.